Sosialisasi Dagusibu Obat Hipertensi dan Diabetes Melitus: Di Desa Semangat Dalam RT 31 Handil Bakti - Ramadhani, Juwita; Erlianti , Karina; Fauzi , Muhammad (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Hypertension and diabetes mellitus are degenerative diseases. Degenerative diseases arise when body cell function declines from a normal to a worse state. Degenerative diseases are still the world's leading cause of death. Overweight or obesity, along with unhealthy lifestyle choices such as consuming low-nutrient instant foods, foods containing preservatives, artificial sweeteners and colorings, and foods high in saturated fat and sodium, are the main causes of this disease. Other factors that contribute to degenerative diseases include high levels of pollution, smoking habits, and excessive alcohol consumption. Therefore, the Community Service Team from the Faculty of Pharmacy in Semangat Dalam Village is conducting community service activities. The team will employ methods such as socialization, discussions, and question-and-answer sessions. The outcomes will help overcome the participants' lack of knowledge regarding the safe and proper ways to obtain, use, store, and dispose of medications.